2021
DOI: 10.1007/s41030-021-00171-8
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Lung Health: Does the Bad Outweigh the Good?

Abstract: Cannabis use is growing, with multiple medical 'indications' and approval for recreational use in many countries. This article will review some of the respiratory complications to cannabis use, which include lung function changes, lung destruction, increased risk of lung and head and neck cancer, and others. These are mostly related to smoking, and the co-administration of nicotine makes the risks a bit difficult to measure. However, with many reports of EVALI, electronic vaping-associated lung injury, being r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Regular cannabis users show histopathologic precursors to malignancy development, findings that are consistent with non-human primate models [ 156 ]. However epidemiological, case–control, and cohort studies have shown no increased risk of cancer from smoking cannabis [ 133 , 157 159 ] and there is a lack of DNA adducts in animal models of chronic cannabis exposure [ 160 ]. Thus, current evidence linking cannabis smoke inhalation and chronic lung disease development remains limited [ 161 , 162 ].…”
Section: Pulmonary Consequences Of Cannabis Inhalationmentioning
confidence: 99%
“…Regular cannabis users show histopathologic precursors to malignancy development, findings that are consistent with non-human primate models [ 156 ]. However epidemiological, case–control, and cohort studies have shown no increased risk of cancer from smoking cannabis [ 133 , 157 159 ] and there is a lack of DNA adducts in animal models of chronic cannabis exposure [ 160 ]. Thus, current evidence linking cannabis smoke inhalation and chronic lung disease development remains limited [ 161 , 162 ].…”
Section: Pulmonary Consequences Of Cannabis Inhalationmentioning
confidence: 99%
“…It is well known that triggers of asthma should be avoided. Adherence to this step is likely also decreased [49] for adolescents. Lack of attention to allergic triggers and avoidance strategies leads to continued allergic inflammation.…”
Section: Treatment Issues Particular To Adolescentsmentioning
confidence: 99%
“…Accordingly, the individual benefit/risk ratio should precede any prescription through an assessment of potential contraindications or limitations. Minimization of combustion-based routes of administration should be emphasized ( 58 , 59 ) and supported by providing appropriate material such as vaporizers ( 60 ).…”
Section: Toward Reciprocity: Where Practice Fuels Knowledge and Vice-...mentioning
confidence: 99%